2011
DOI: 10.1093/bja/aer265
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen delivery through high-flow nasal cannulae increase end-expiratory lung volume and reduce respiratory rate in post-cardiac surgical patients

Abstract: This study suggests that HFNCs reduce respiratory rate and improve oxygenation by increasing both EELV and tidal volume and are most beneficial in patients with higher BMIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
365
4
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 441 publications
(410 citation statements)
references
References 29 publications
29
365
4
12
Order By: Relevance
“…FiO 2 values administered via NHF are more stable and higher than those of standard oxygen delivery systems [1], because NHF can generate high flow rates up to 60 L·min −1 that can match or even exceed the patient's inspiratory flow demand, thus reducing entrainment of room air and dilution of administered oxygen [3,4]. In addition, these high flow rates create a positive airway pressure which linearly correlates with the administered flow rate [3][4][5][6][7][8]. For every 10 L·min −1 increase in gas flow, the mean airway pressure increases by ∼0.69 cmH 2 O in the mouth-closed position and by 0.35 cmH 2 O in the mouth-open position [8].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 3 more Smart Citations
“…FiO 2 values administered via NHF are more stable and higher than those of standard oxygen delivery systems [1], because NHF can generate high flow rates up to 60 L·min −1 that can match or even exceed the patient's inspiratory flow demand, thus reducing entrainment of room air and dilution of administered oxygen [3,4]. In addition, these high flow rates create a positive airway pressure which linearly correlates with the administered flow rate [3][4][5][6][7][8]. For every 10 L·min −1 increase in gas flow, the mean airway pressure increases by ∼0.69 cmH 2 O in the mouth-closed position and by 0.35 cmH 2 O in the mouth-open position [8].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Analysis of the pressure generated during different parts of the respiratory cycle demonstrated that higher pressures are obtained during expiration than inspiration, which are flow dependent [9]. This mechanism resembles the application of positive end-expiratory pressure (PEEP), and it results in recruitment of the atelectatic areas and thus increase of end-expiratory lung volume (EELV) by ∼25% [5]. This effect is more pronounced in subjects with higher body mass index (BMI), regardless of body position [5,10].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this technique allows for the titration of the fraction of inspired oxygen as well. [1][2][3] High-flow oxygen therapy has been shown to result in better comfort and oxygenation in patients with acute respiratory failure in previous studies. However, evidence for high-flow oxygen therapy on intubation rates and mortality is lacking.…”
Section: Division Of Pulmonology Chris Hani Baragwanath Academic Hosmentioning
confidence: 99%